2009
DOI: 10.1007/s11695-009-9912-9
|View full text |Cite
|
Sign up to set email alerts
|

Adipokine Serum Levels Are Related to Liver Histology in Severely Obese Patients Undergoing Bariatric Surgery

Abstract: Serum adiponectin and resistin levels are related to liver histology in bariatric patients and may be indicative of the histological severity of NAFLD and the extent of hepatic steatosis, respectively. Serum leptin levels are not informative of underlying liver histology in severely obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 59 publications
(87 reference statements)
1
32
0
Order By: Relevance
“…Adipokines have been shown to be related to liver pathology and also in morbid obesity (15). Chemerin levels are significantly elevated in morbidly obese women characterized by a significant activity score for nonalcoholic fatty liver disease and fibroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Adipokines have been shown to be related to liver pathology and also in morbid obesity (15). Chemerin levels are significantly elevated in morbidly obese women characterized by a significant activity score for nonalcoholic fatty liver disease and fibroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent study showed lower levels of resistin in NASH patients compared with those with simple steatosis [149]. In other studies no differences in resistin concentrations were found between NAFLD patients and matched controls [150][151][152].…”
Section: Resistinmentioning
confidence: 99%
“…Even further upstream of this are endocrine and paracrine mechanisms that can promote lipogenesis. Adiponectin is a key insulin sensitizer, which is often decreased in insulin resistant states [9]. Adiponectin is an adipokine and a PPAR-target.…”
Section: Systemic Metabolic Disturbances That Contribute To Steatohepmentioning
confidence: 99%